Assessment of Bronchodilator Response in Various Spirometric Patterns - Mehrparvar, Amir Houshang (National Research Institute of Tuberculosis and Lung Disease, 2013)
BACKGROUND: Spirometry is a physiologic test that measures the volume of air an individual inhales or exhales and the rate at which the volume is changed as a function of time. Bronchodilator response, as a beneficial test for diagnosis of bronchial responsiveness is measured using the percent change from baseline and absolute changes in forced expiratory volume in 1 second and/or forced vital capacity. In this study we aimed to assess the increase in spirometric parameters in patients with symptoms of asthma regardless of spirometric pattern. MATERIALS AND METHODS: In this cross-sectional study bronchodilator test was performed in individuals with dyspnea, cough or wheezing and the mean increase in various spirometric parameters was measured and compared among individuals with different spirometric patterns. RESULTS: Among all individuals 24.5% responded to bronchodilator. Forced expiratory volume in 1 second was the parameter with the most frequent response to bronchodilator. Patients with mixed pattern had the highest frequency of response to bronchodilator. Response to bronchodilator was more than 50% in most mid flow volumes. CONCLUSION: Some patients with symptoms of asthma may show restrictive or mixed pattern in spirometry which may respond to bronchodilator administration.